A Propedêutica hegeliana e a simbologia das mandalas: uma experiência na iniciação filosófica do ensino médio. - ERIKA CIPOLLA (2022)
The discussions and documents that guide educational practices on the national scene have frequently placed the topic of integral education in their agenda. This organic education requires proposals that reflect on this process as well as its effect, that is, on individuals capable of inserting themselves in the collective and social sphere in a participatory, critical and transformative manner. The intellectual repertoire provided by the teaching of philosophy, integrated with other knowledge accessible at school, represent a possible path to the awakening of a subject who recognizes himself as belonging and, therefore, of a subject who is committed to the improvement of the social process. Starting from a context marked by the search for an authentic cultural identity, Hegel develops a foundational work that takes into account the complexity of human formation, where school education is inevitably inserted. In addition, the awakening of the conscience that wants to explore the concepts of the world, but that goes through several setbacks until it can be effected in the conciliation between what is known and who knows, can be provided by the philosophical experience. The Philosophical Propaedeutics, a work used as the main reference for this research, brings together notes and plans from Professor Hegel's classes, through which the author demonstrates a vehement concern to bring the school educational process closer to his refined philosophical theory. In the course of this investigation, we want to expand the possibilities of inserting the Hegelian theory in the proposed curriculum for the study of philosophy in high school. Our sequent goal is to choose concepts, present in the Hegelian system, which reflect the centrality of an individual path committed to an ethical-social coexistence. This research aims to offer to the philosophy professor an integrative didactic experience, reconciling the study of central elements of the sophisticated Hegelian work with a unique creative expression, that of mandalas. By uniting the theoretical exploration of Bildung and the path of consciousness, developed by Hegel, to the meanings of mandalas, our goal is to develop a practice that enables conceptual concatenation through an aesthetic experience. The four chapters developed in this work intend to conduct the reader through the main paths articulated in this process, providing opportunities to get in touch with the constant dialogue undertaken between the two elementary dimensions of this study. Mandalas, such as the Hegelian Philosophy, generally represent unexplored environments by the youngest, encouraging the practice suggested by the previous theoretical background, elaborated in this work from a sequence of classes that combine conceptual engagement and artistic exercise. The constituent similarities of the mandalas and of the highlighted aspects of Hegel's theory were observed from a patient and incessant process of search for an encounter of the being with the world. The different meanings combined with the vivacity of the mandalas symbology can pleasantly connect the access of young minds to the density of the philosophical concepts proposed in this research, through an intense theoretical and reflective experience of the consciousnesses involved in this process of exchanges and mediations.